ANALISIS KEBUTUHAN (NEED ANALYSIS) UNTUK PENGEMBANGAN LEMBAR KERJA SISWA (LKS) DENGAN BANTUAN DIGITAL MIND MAPS - Apriza Fitriani; Rukiah Lubis; Sulianti Angrum Maningsih (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Teaching materials are an important part of the learning process, one of which is the Student Worksheet (LKS). An educator needs to increase creativity in preparing teaching materials to be delivered. Teaching materials used by students need to follow the development of science and technology. A digital mind map is a mind map that is packaged in digital form that displays brief lesson notes in the form of a mind map with the help of the mindomo application. This needs analysis was carried out to find out the needs needed in the Student Worksheet (LKS), and responses regarding the development of LKS with the help of digital mind maps. This type of research method is descriptive qualitative research. Research data was obtained by observation, interviews, and distributing questionnaires. The results obtained from this analysis are the responses of teachers and students to the development of worksheets with the help of digital mind maps are quite good. The worksheets used by educators are monotonous but understandable, there is no digital mind maps task to increase student creativity. Students also agree that there is an interesting, easy-to-understand LKS development by using their Android smartphones. Therefore, the data from this needs analysis becomes a preliminary study on the development of LKS with the help of digital mind maps, then it is developed into an LKS with the help of digital mind maps that will be used.Kata Kunci: Analisis Kebutuhan, Lembar Kerja Siswa (LKS), Digital Mind Maps